Evaluating user experience of a mobile website and redesigning its user interface using goal-directed design method - Aang Subiyakto; Muhammad R. Alghifari; Nuryasin N.; Muhammad Q. Huda; Nashrul Hakiem; Viva Arifin; Dwi Yuniarto; Hadi Rahman; Thosporn Sangsawang; Naeem Atanda Balogun (International Journal of Informatics and Communication Technology (IJ-ICT), 2026)
This study evaluated the usability of the user interface (UI) of a mobile website using its user experience (UX) perspectives. The website serves as an information portal intended for access via smartphones and other handheld devices. The objective of the study was to assess the usability of its current interface, redesign it using the goal-directed design (GDD) method, and compare the usability performance before and after the redesign. The study was conducted in five main steps using the cognitive walkthrough, think-aloud, post-study system usability questionnaire (PSSUQ), and interview techniques with five representative participants and 50 respondents. The most important findings of the study were that the redesigned mobile website showed improved usability of the website, as indicated by increased effectiveness and efficiency values, enhanced PSSUQ satisfaction scores, and more positive user feedback.